2014
DOI: 10.1186/s12935-014-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

Rutin mediated targeting of signaling machinery in cancer cells

Abstract: Progress in our understanding of molecular oncology has started to shed light on dysregulation of spatio-temporally controlled signaling pathways, inactivation of tumor suppressor genes, tumour and normal stem cell quiescence, overexpression of oncogenes, extracellular and stromal microenvironments, epigenetics and autophagy. Sequentially and characteristically it has been shown that cancer cells acquire the ability to escape from apoptotic cell death, proliferate uncontrollably, sustain angiogenesis and tactf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 45 publications
(40 reference statements)
2
46
0
1
Order By: Relevance
“…On the other hand, rutin ( 3 ) has been reported as anticancer agent by inducing apoptosis and cell cycle arrest in murine leukemia WEHI-3 cells [41]. It was also reported that rutin ( 3 ) had the potential to kill the breast cancer cells in MDA-MB-231 cell line [42]. Based on the findings, the current study supports the hypothesis that antimicrobial, anticancer and antioxidant activities of C. angustifolia are due to at least in part to the presence of isolated flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, rutin ( 3 ) has been reported as anticancer agent by inducing apoptosis and cell cycle arrest in murine leukemia WEHI-3 cells [41]. It was also reported that rutin ( 3 ) had the potential to kill the breast cancer cells in MDA-MB-231 cell line [42]. Based on the findings, the current study supports the hypothesis that antimicrobial, anticancer and antioxidant activities of C. angustifolia are due to at least in part to the presence of isolated flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various antitumor studies have been reported for rutin in rodents. For instance, a prior study has reported the antitumor effect of rutin in nude mice bearing SW480 colon cancer cells (12). …”
Section: Discussionmentioning
confidence: 99%
“…For instance, rutin supplements are touted as a natural remedy to improve vascular disorders (11). Additionally, it showed anti-oxidant, anti-inflammatory, chemopreventive, and anticancer in vitro and in vivo activities (12). Reportedly, rutin modulates a wide range of intracellular signaling cascades including; the intrinsic pathway mediated apoptosis in leukemia K562 cells and down-regulation of the levels of inflammatory markers like tumor necrosis factor alpha (TNF-​α) and cyclooxygenase-2 (COX-​2) (13).…”
Section: Introductionmentioning
confidence: 99%
“…Of the rooibos polyphenols very little is known about the anti-inflammatory effects of aspalathin, a dihydrochalcone and major flavonoid present in unoxidized rooibos. Quercetin and rutin have been reported to effect apoptosis in cancer cells including UVB-irradiated HaCaT keratinocytes [54,55]. Iso-orientin and vitexin are also known to effect apoptosis in cancer cells by disrupting the mitochondrial signalling pathways [56,57].…”
Section: Discussionmentioning
confidence: 99%